Short Communication: Molecular characteristics and phylogenetic relationships of silurid catfishes (Kryptopterus, Ompok and Phalacronotus) from the Kampar River, Indonesia, based on the cytochrome b gene - Roza Elvyra; DEDY DURYADI SOLIHIN; RIDWAN AFFANDI; MUHAMMAD ZAIRIN JUNIOR; MEYLA SUHENDRA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Elvyra R, Solihin DD, Affandi R, Junior MZ, Suhendra M. 2020. Short Communication: Molecular characteristics and phylogenetic relationships of silurid catfishes (Kryptopterus, Ompok, and Phalacronotus) from the Kampar River, Indonesia, based on the cytochrome b gene. Biodiversitas 21: 3539-3546. The study of molecular characteristics and phylogenetic relationships among silurid catfishes (Kryptopterus, Ompok, and Phalacronotus) is very scarce. Existing data are mostly based on morphological characters. Genetic markers among Kryptopterus, Ompok, and Phalacronotus can be analyzed by exploring the nucleotide and amino acid sequences of the mitochondrial cytochrome b gene region (906 base pairs). This study aims to identify molecular characteristics and phylogenetic relationships of silurid catfishes from the Kampar River based on the cytochrome b gene. This research examined 14 silurids of four species from three genera in the Kampar River of Indonesia. Molecular phylogenetic trees were constructed using the neighbor-joining method. This study revealed that three amino acid sites can be used as specific genetic markers for characterizing Kryptopterus limpok. They are E (glutamic acid) at site 123, V (valine) at site 155, and M (methionine) at site 156. Two amino acid sites can be used as specific genetic markers of Ompok spp., A (alanine) at site 201 for O. hypophthalmus, and S (serine) at site 282 for O. eugeneiatus. Two amino acid sites, I (isoleucine) at site 197 and L (leucine) at site 284, can be used to identify Phalacronotus apogon from the Kampar River, Indonesia. The phylogram results based on genetic distance (p-distance) from nucleotide cytochrome b sequences generally showed that intraspecies of K. limpok, O. eugeneiatus, O. hypophthalmus and P. apogon from the Kampar River formed relationship groups within each species supported by high bootstrap values. Additionally, based on genetic distance, K. limpok data from the Kampar River samples and GenBank formed one relationship group within species of K. limpok with a high bootstrap value. This study proves that cytochrome b gene can be used to identify molecular characteristics and phylogenetic relationships of K. limpok, O. eugeneiatus, O. hypophthalmus, and P. apogon from the Kampar River, Indonesia.